Neurotization from Two Medial Pectoral Nerves to Musculocutaneous Nerve in a Pediatric Brachial Plexus Injury - Yu, Dong-Woo (The Korean Neurosurgical Society, 2012)
Traumatic brachial plexus injuries can be devastating, causing partial to total denervation of the muscles of the upper extremities. Surgical reconstruction can restore motor and/or sensory function following nerve injuries. Direct nerve-to-nerve transfers can provide a closer nerve source to the target muscle, thereby enhancing the quality and rate of recovery. Restoration of elbow flexion is the primary goal for patients with brachial plexus injuries. A 4-year-old right-hand-dominant male sustained a fracture of the left scapula in a car accident. He was treated conservatively. After the accident, he presented with motor weakness of the left upper extremity. Shoulder abduction was grade 3 and elbow flexor was grade 0. Hand function was intact. Nerve conduction studies and an electromyogram were performed, which revealed left lateral and posterior cord brachial plexopathy with axonotmesis. He was admitted to Rehabilitation Medicine and treated. However, marked neurological dysfunction in the left upper extremity was still observed. Six months after trauma, under general anesthesia with the patient in the supine position, the brachial plexus was explored through infraclavicular and supraclavicular incisions. Each terminal branch was confirmed by electrophysiology. Avulsion of the C5 roots and absence of usable stump proximally were confirmed intraoperatively. Under a microscope, neurotization from the musculocutaneous nerve to two medial pectoral nerves was performed with nylon 8-0. Physical treatment and electrostimulation started 2 weeks postoperatively. At a 3-month postoperative visit, evidence of reinnervation of the elbow flexors was observed. At his last follow-up, 2 years following trauma, the patient had recovered Medical Research Council (MRC) grade 4+ elbow flexors. We propose that neurotization from medial pectoral nerves to musculocutaneous nerve can be used successfully to restore elbow flexion in patients with brachial plexus injuries.